2022
DOI: 10.3390/agronomy12051107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Mowing on Biomass Composition in Pannonian Dry Grasslands

Abstract: This study is focused on the vegetation of seminatural dry grasslands. These grasslands are valuable with large biodiversity; however, their long-term preservation requires regular conservation management. This report demonstrates the results of a 13-years mowing experiment, designed to suppress the spread of an unpalatable grass species, Calamagrostis epigejos. The study site was located in mid-successional grasslands, in the Western-Cserhát, near Rád, Northern Hungary. The experimental design consisted of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
6
0
5
Order By: Relevance
“…Akhani and Roalson, and Cenchrus echinatus L. and other species, started to appear in the mowed desert grassland, because mowing removes some biomass from aboveground parts of tall plants and damages their vegetative organs, photosynthetic capacity, and competitiveness [11,12], and mowing reduces soil organic matter (C and N) by removing aboveground biomass, thus reducing plant residues that can return to soil and photosynthetic C transfer to roots. Additionally, mowing eliminated the shelter provided by standing litter and the accumulation of litter in the community, enhancing the light and water conditions for lower-level plants, expanding the opportunities for new seeds to come into contact with the soil, and fostering the growth and development of annual or biennial dwarf plants [40]. It was also confirmed that mowing disturbance can change the interspecific relationship by increasing spatial heterogeneity [39], thereby changing diversity of communities, and reducing litter is also beneficial for germination of dormant seeds in soil and the regeneration and reproduction of species [41].…”
Section: Discussionmentioning
confidence: 99%
“…Akhani and Roalson, and Cenchrus echinatus L. and other species, started to appear in the mowed desert grassland, because mowing removes some biomass from aboveground parts of tall plants and damages their vegetative organs, photosynthetic capacity, and competitiveness [11,12], and mowing reduces soil organic matter (C and N) by removing aboveground biomass, thus reducing plant residues that can return to soil and photosynthetic C transfer to roots. Additionally, mowing eliminated the shelter provided by standing litter and the accumulation of litter in the community, enhancing the light and water conditions for lower-level plants, expanding the opportunities for new seeds to come into contact with the soil, and fostering the growth and development of annual or biennial dwarf plants [40]. It was also confirmed that mowing disturbance can change the interspecific relationship by increasing spatial heterogeneity [39], thereby changing diversity of communities, and reducing litter is also beneficial for germination of dormant seeds in soil and the regeneration and reproduction of species [41].…”
Section: Discussionmentioning
confidence: 99%
“…Általánosságban elmondható, hogy a területek fajszáma drasztikusan lecsökkent. Tájidegen, agresszív kompetítor 2010-ben még nem volt megtalálható, azonban az újabb felvételezések során azzal voltunk kénytelenek szembesülni, hogy az egykori legelőterületen a magas aranyvessző (Solidago gigantea) kezd uralkodóvá válni (Besnyői, 2012a, b;Fülöp et al, 2021;Bódis et al, 2021;Penksza és Saláta, 2022;Penksza et al, 2021;Fűrész et al, 2022;Rácz et al, 2021;Péter et al, 2020;Hajnáczki et al, 2014Hajnáczki et al, , 2018Hajnáczki et al, , 2021Házi et al, 2009Házi et al, , 2011Házi et al, , 2012Házi et al, , 2022Schaffers, 2002).…”
Section: Legeltetésunclassified
“…Ezen túl az elmúlt időszakban egyre inkább újabb gyepek telepítése és fenntartása folyik (Török et al, 2011a;Vida et al, 2008), ami egyben napjaink egyik leggyakrabban alkalmazott élőhely-rekonstrukciós beavatkozásai közé tartozik. A kaszálásnak a visszagyepesítést követő szakaszban van jelentős szerepe, mivel hatására visszaszorulnak a gyomok és a betelepülő kísérő fajok megjelenése nő (Vida et al, 2008;Török et al, 2010Török et al, , 2012aTörök et al, , b, 2016Billeter et al, 2007;Gerard et al, 2008;Kelemen et al, 2013a, b), valamint elszegényedő fajgazdagságú gyepekben segíti a diverzitás-csökkenésének a megállítását (Szabó et al, 2007;Házi et al, 2009Házi et al, , 2011Házi et al, , 2022Hajnáczki et al, 2021). A legeltetés azon túl, hogy a visszagyepesítést követően javasolt, önállóan is alkalmas a gyepterületek kezelésére, miután a gyepek váza már kialakult (Penksza et al, 2008;Szentes et al, 2007aSzentes et al, , b, 2008Szentes et al, , 2012aSzentes et al, , b, 2022Kiss et al, 2011).…”
Section: Bevezetésunclassified